2019
DOI: 10.21203/rs.2.12084/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic accuracy of QuickVue® Dipstick Strep A test and its effect on antibiotic prescribing in children in the United Arab Emirates

Abstract: Background: Unnecessary antibiotic prescription to patients with upper respiratory tract infections (URTIs) has led to the increase in antibiotics resistant bacteria rates. In this study, we evaluated the diagnostic accuracy of QuickVue® Dipstick Strep A test (QV-SAT) in children presenting with acute pharyngotonsillitis and its effect on antibiotic prescribing. Methods: A single-gated diagnostic accuracy study of children with fever, runny nose, and tonsillitis presenting to a paediatric clinic between Marc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
4
2
Order By: Relevance
“…This could be attributed to the higher sensitivity of the FIA-RADT compared to the standard culture method as discussed below. The sensitivity and specificity of the FIA-RADT in our study were very high; however, the percentages were lower than those reported in a recent study from the United Arab Emirates (UAE) [21]. This can be explained by the fact that 70 % of the population in the UAE study comprised children under 5 years of age, who are known to have low incidence of group A streptococcal pharyngitis.…”
Section: Discussioncontrasting
confidence: 88%
“…This could be attributed to the higher sensitivity of the FIA-RADT compared to the standard culture method as discussed below. The sensitivity and specificity of the FIA-RADT in our study were very high; however, the percentages were lower than those reported in a recent study from the United Arab Emirates (UAE) [21]. This can be explained by the fact that 70 % of the population in the UAE study comprised children under 5 years of age, who are known to have low incidence of group A streptococcal pharyngitis.…”
Section: Discussioncontrasting
confidence: 88%
“…Among our patients, the prevalence of GAS pharyngitis was 30.9%. This is higher than the previously reported prevalence of 14% between 2004 and 2006 [23] and 20.6% between 2016 and 2018 [22] among children in the United Arab Emirates. The increase in reported prevalence in our current study could represent a referral bias of sicker children presenting to the ER rather than to an outpatient clinic.…”
Section: Discussioncontrasting
confidence: 73%
“…This is the first study evaluating the accuracy of A-SAT in the Middle East. We have previously reported a high diagnostic accuracy of rapid streptococcal antigen tests, comparable to throat culture, when performed by an attending pediatrician in the outpatient clinic setting in the United Arab Emirates [22,23]. Unfortunately, those findings were not generalizable to a "real world" scenario where children are often assessed by general physicians and throat samples are taken by non-pediatric healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations